THE INFLUENCE OF INSTRUCTIONAL SUPERVISION ON TEACHER PEDAGOGICAL COMPETENCE AND ITS IMPACT ON STUDENT ACHIEVEMENT - Febrina, Weli; Defi, Wahyu Fitrina; Bestri, Rafikah; Rifma, Rifma; Sulastri, Sulastri (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2024)
Study carried out at the Nan Sabaris District Public Elementary School Padang Pariaman Regency. Study aim For know the influence of instructional supervision to teacher performance and towards performance studentwƐƐƐa. As one of the component main in management education, supervision instructional works For increase teacher competence which in turn also has an impact to performance student. Approach study This is approach quantitative with path analysis data analysis techniques. Research result show that there is influence significant Good in a way direct or not direct instructional supervision and competency variables pedagogy to performance student.